ANALISIS PENGENDALIAN INTERNAL ATAS PERSEDIAAN BARANG DAGANGAN PADA TOKO ALFAMART SAT BOOM BARU PALEMBANG - . Sahila; Kusminaini Armin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
Alfamart SAT Boom Baru Palembang is one of the mini markets under the auspices of PT. Sumber Alfaria Trijaya, Tbk. (Alfamart) Palembang Branch. As with companies in general. Alfamart engaged in the retail sector also has certain targets to be achieved in an effort to grow and develop into a leading company in their field. To achieve this, in addition to increasing productivity, it is necessary to have good control over the control of merchandise in Alfamart stores, because it is closely related to the effectiveness and operational efficiency of the company.The results of the study are that the control environment has been running with the existence of an organizational structure and clear division of tasks. Risk assessment runs well using computerized technology. Activities run well because the receipt and expenditure of goods is done by authorizing authorized shop officials and physical inspection of merchandise carried out routinely. Information and communication went well between the shopkeepers, shop assistant assistants, and sales clerks and cashiers, who routinely conducted briefings before starting shop operations and the handover between shop officials every shift shift. Monitoring (supervision) of all activities related to merchandise inventory is carried out according to the authorization of shop officials and Regional Coordinators who routinely make visits to stores.In the future, it is recommended that PT. Sumber Alfaria Trijaya, Tbk. (Alfamart) makes a policy to carry out a physical inspection of merchandise (stock taking) thoroughly S.O. Grand regularly, for example every six months, not only when there is a change of head shop. Keywords: Environmental Control, Risk Interpretation, Control Activities, Information and Communication, Monitoring